Modal Sosial Siswa Miskin: Studi mengenai Kekuatan Jaringan Sosial, Kepercayaan, dan Norma di Kalangan Siswa Miskin - Nanang Martono; Elis Puspitasari; Lisnawati Lisnawati (Society, 2023)
This study examines the social capital of impoverished students who possess limited economic resources. To thrive in school, these students heavily rely on strong social capital. Social capital is crucial for impoverished students as it enables them to interact effectively with teachers and peers. The study was conducted in four high schools located in Temanggung, Cilacap, Purbalingga, and Kebumen Regencies, Central Java Province, Indonesia. The study respondents were students from impoverished families, selected through a simple random sampling method, comprising 30% of the impoverished students in those schools. The findings revealed that a significant majority of the respondents exhibited high social capital. This was evidenced by the extent of their social networks, which encompassed close relationships with peers from both their own and other schools. Consequently, they felt accepted and integrated within their social groups. Furthermore, these students adhered to prevailing social norms within their school and peer circles, further facilitating their acceptance. Impoverished students also managed to gain the trust of both their friends and teachers. This was exemplified by their frequent involvement in assisting classmates with school assignments. However, despite possessing these positive social attributes, they were rarely allowed to hold specific positions within the class or organizational structures. Additionally, they were seldom selected to represent the school in various competitions.